FROM CENTRAL ASIA TO GREAT CENTRAL ASIA: HE GOALS AND ADJUSTMENTS OF U.S. CENTRAL ASIAN STRATEGY - Guang TIAN, Robert (CENTRAL ASIA AND THE CAUCASUS, 2009)
To penetrate and maintain peaceful development of the Central Asian region is a consistent goal of the United States for its international interests. With the 9/11 event as the baseline, since 2001 America’s awareness of the strategic im-portance of Central Asia and the latter’s weight in U.S. global strategy has been greatly changed. According to Charles Manes, the 9/11 terrorist attack enabled the U.S. to “discover Central Asia.”1 As a result of this discovery the United States effectively gained a foothold in Central Asia. However, the U.S. has been so impatient that it made a policy mistake. In supporting the Color Revolution in order to change the political system in Central Asian countries, it promoted democratization in the region in too great a rush. Facts have proved that the Color Revolution model is not suitable for this area. The U.S. interference in Central Asia has caused some suspicion in Central Asian countries which in turn has affected relations between the United States and Central Asian countries. Due to their suspicion of aggressive U.S. actions in this region, Central Asian countries have reported a steady development in their cooperation with Russia and China.The operation of the Shanghai Cooperation Organization (SCO) has been very impressive and successful. It set a strong force to challenge the U.S. strategy in the region; for instance, on 5 July,2005, the SCO issued a declaration calling for the United States, though not explicitly, to set a timeline for withdrawing its military forces from Karshi-Khanabad Air Base, located in southern Uzbekistan.2